Emergency Department Utilization in Children <36 Months Is Not an Independent Risk Factor for Maltreatment. (6th November 2016) - MacNeill, Emily C.; Cabey, Whitney; Kluge, Robert; Norton, James; Mitchell, Alice M.
Abstract: Background and Objectives: Early childhood high‐frequency use (HFU) of the emergency department (ED) has been endorsed as a marker for increased risk of child maltreatment. In a prior analysis of pediatric ED (PED) visits by 16, 664 children, 0–36 months old, we defined early childhood HFU (the 90th percentile) as five or more visits. The purpose of this study was to follow HFU patients to determine if they had a higher likelihood of reported maltreatment. Methods: This is a single‐center, cross‐sectional, observational study of the association between PED use in early life and subsequent intervention by child protective services (CPS). CPS data were obtained from a Department of Social Services database for subjects meeting criteria for PED HFU as well as sex, race, and ethnicity‐matched controls. Multivariable analyses were performed to assess if HFU was independently associated with child maltreatment. Results: While CPS involvement was more highly represented in the group with PED HFU, so were many confounding variables such as African American race, history of hospital admissions, and social work consultations in the PED for any reason. HFU, by itself, is not a risk factor for a major intervention by CPS. Conclusions: In efforts to identify children at risk for maltreatment, objective assessments such as PED utilization are potential markers to utilize to aid in recognition. Unfortunately, there are many risk factors for increased PED utilization that act as confounders for this marker. Future work is necessary to identify children at risk for maltreatment in the ED.